Carol Shields's The Republic of Love: Fragmentation and Narration - Polić, Vanja (2007)
The paper analyses Carol Shields's novel "The Republic of Love" with regard to the notion of individual identity as represented through the specific narrative structure of the novel.
Projekt MZOS
ENG